Bone appétit : 50 clean recipes for healthier, happier dogs - Robertson, Debora (Harper Design, 2019)
Forget processed store-bought food--feed your dog a nutritious, balanced diet that uses healthy quality ingredients with this charming full-color illustrated guide with fifty great recipes for your beloved companion. Modern dog people only want the best for their canine companions, and that extends to the food they eat. With Bone Appétit, you control the ingredients and the portions to feed your dog a practical, nutritious, and balanced diet--all from scratch!